Alternativa de controle pós-colheita da antracnose em banana (Musa ssp.) - Santos, Maria Denise Rodrigues dos (2017)
The banana (Musa spp.) is one of the most consumed fruits in Brazil, and one of the main causes of postharvest losses is the occurrence of diseases, highlighting anthracnose caused by Colletotrichum musae fungus. Currently the main method of control is the use of synthetic fungicides that in contrast to its effectiveness in combating pathogen, causes losses to man and environment. Thus, the present work was developed with the objective of determining the potential of essential oil from mentha, camphor, ginger, spearmint, citronella, eucalyptus, sunflower, rosemary, clove and grape seeds in control of C. musae, as well as determine any effect as inducers of resistance and quality of postharvest of the fruits treated. For that, it was developed two experiments. In the first one, the fruits of Pacovan variety acquired from producers in the region of brejo paraibano were treated with solutions from different oils in concentrations 0,5%; 1,0%; 2,0% e 2,5%. Chitosan (12g L-1 ), Tiabendazole fungicide (4 mL L 1 ) and distilled water were used as control treatment. Each treatment was compound for four repetitions with three fruits per repetition. During eleven days, four days after the fruits treatment, it was evaluated the severity using a diagrammatic scale and with the grades of severity was calculated the area bellow the progress curve (AACPD) and the protection percentage. In the last day of evaluation was done the collect of tissues from the treated fruits with oils in concentration 2% to determination of enzyme activity of phenylalanine ammonia lyase (PAL), peroxidase (POD) and polyphenoloxidase (PPO). In the second experiment was evaluated the physical and chemical characteristics of the treated fruits with essential oils of spearmint, eucalyptus, grape seed and citronella in concentration of 2% and chitosan, fungicide and distilled water sterilized as controls. The experiment was compound for four repetitions per treatment, contain three fruits per repetition. The evaluations were realized in four periods with ranges of three days. The postharvest analyses evaluated were: lose of mass, total soluble solids (SST) titratable acidity (AT), colour, firmness (N) and potential of hydrogen (pH). The grape, citronella, mint and eucalyptus oils were distinguished in reducing the severity of the disease, as well as in the activity of the enzymes studied and maintained the good quality of the fruit.